Home advantage: Performance effects in female collegiate Division I gymnasts - Baghurst, T. M. (Research Quarterly for Exercise and Sport, 2008)
The purpose of this study was to investigate the performance effects of competing at home or away in female collegiate Division I gymnastics. Participants were teams GY- 15) ranked in the top 25 nationally at the end of each regular season during the period of 2003 LO 2007 with the exclusion of 2005. Data were collected from all regular season home and away meets during this period. A repeated measures analysis of variance revealed home scores to be significantly higher than away scores. Additionally, with die introduction of the Judges' Assignor System (JAS) in 2005, team scores at home and away were compared before and after its introduction. Team scores were .significantly higher at home prior to and following the introduction of JAS. However, scores were found to he significantly lower at both home and away with JAS. The results of this study suggest that teams perform significantly better at home than away. In addition, the findings suggest that JAS has significantly reduced gymnastics scores at home and away, yet have not significantly altered the effects of competing away from home. Findings are discussed in light of current research and application for coaches and officials is provided.